Fullfillment of Spiritual Needs on Depression and Anxiety Patient at Dr.Soekardjo Hospital in Tasikmalaya - Wawan Rismawan; Sri Ayuningsih; Evi Irmayanti (Publikasi Indonesia, 2022)
Introduction: Disorders of the soul is a significant disruption The Data found on the World Health Organization reports that depression sufferers globally estimated there are 350 million people. In Indonesia the Data Riskesdas 2013 showed interference prevalence of mental emotional indicated with symptoms of depression and anxiety for over 15 years and reach about 14 million people or 6% of the total population Indonesian. While the prevalence of disorders such as schizophrenia, heavy soul reaching about 400,000 people or as much as 1.7 per 1,000 inhabitants. The aims of Uto know the description of the compliance spiritual needs in psychiatric HOSPITALS poly dr. Soekardjo Tasikmalaya. Research methods: Research Use descriptive method. Populations and samples in this study is patients with depression and anxiety sufferers in poly psychiatric HOSPITALS Dr. Soekardjo Tasikmalaya Town as much as 81 respondents by using the sampling method Non Probability Sampling Incidental Sampling with Incidental Sampling. Engineering data collection using the questionnaire. Research results: based on the research results of the spiritual needs of the majority of patient compliance is good as many as 70 respondents (86.4%). Summary: that patient's capabilities in General in spiritual fulfillment it is good for as much as 70 respondents (86.4%).